The relationship of work stress and job insecurity with workplace safety compliance, job satisfaction and commitment in a mine - Masia, Uanda (North-West University, 2010)
The reduction of workplace accidents and improvement of workplace safety is a concern for most mining houses. Pressure from the labour movement and legislative requirements do not make the burden any lighter. There are circumstances directly and indirectly relating to accidents and therefore a need to obtain an in-depth analysis of underlying causes of accidents in order to draw relevant conclusions exists. There are workplace environmental matters as well as individual attitudinal issues that need to be addressed. The objective of this study is to investigate the relationship of work stress and job insecurity with safety compliance, job satisfaction and commitment in a mine. A cross-sectional survey design was used with an availability sample (n=158). A survey booklet including a biographical questionnaire, scales on job insecurity, job satisfaction, affective organisational commitment, workplace accidents and safety compliance as well as a work stress measure comprising dimensions of role clarity, conflict and overload was administered. The results indicated that when miners experience work stress and job insecurity, their safety compliance is low. Job satisfaction was found to be a positive predictor of safety compliance among miners.
Thesis (M.A. (Industrial Psychology))--North-West University, Potchefstroom Campus, 2010.
Keywords: Work stress; Job insecurity; Job satisfaction; Organisational commitment; Workplace accidents; Workplace safety compliance; Occupational safety